Association between dietary inflammatory index and anthropometric indicators of adiposity in Brazilian adolescents. Issue 5 (6th February 2023) - Blaudt, Luana Senna; de Souza Lopes, Taís; de Moura Souza, Amanda; Yokoo, Edna Massae; da Rocha, Camilla Medeiros Macedo; Pereira, Rosangela Alves
Summary: Background: Diet may play a role in the regulation of obesity‐related low‐grade chronic inflammation. Objective: Assess the association of the Dietary Inflammatory Index (DII) with anthropometric indicators of adiposity in Brazilian adolescents. Methods: Data were collected from 71 740 adolescents (12–17 years old) examined in the Study of Cardiovascular Risks in Adolescents. Food consumption was assessed by means of one 24‐h dietary recall, and DII was estimated using 39 food parameters. The body mass index (weight/height 2 ) for age and sex was used to define overweight (>1 z ‐score). Abdominal obesity was indicated by waist circumference (WC) values >80th percentile and waist‐to‐height ratio (WHtR) > 0.50. The association between DII and anthropometric indicators was assessed using logistic regression models. Results: The mean DII score was higher in girls than in boys (0.77; SD = 0.04 vs. 0.04; SD = 0.05). Adolescents in the 4th quartile of DII, compared with those in the 1st quartile, had increased odds of being overweight (boys: OR = 1.76; 95% CI: 1.37; 2.25; girls: OR = 1.63; 95%CI: 1.36; 1.95), having abdominal obesity (boys: OR = 1.61; 95%CI: 1.33; 1.95; girls: OR = 1.73; 95%CI: 1.48; 2.03), and having high WHtR (boys: OR = 1.91; 95%CI: 1.52; 2.39; girls: OR = 1.75; 95%CI: 1.46; 2.11). Conclusions: The findings showed a direct association between the dietary inflammatory potential measured by DII and adiposity.